Development of a post-traumatic growth scale for a sample of adults in Syria (The International Journal for Scientific Research, 2025)
This study aimed to develop a scale for assessing post-traumatic growth and to examine the growth levels among a sample of traumatized adults in Syria who had experienced displacement, detention, loss, homelessness, and significant financial hardship. The scale development and psychometric evaluation sample consisted of 142 individuals, while the sample used to assess post-traumatic growth levels included 120 participants.The scale construction involved multiple steps, including item selection and the extraction of validity indicators through both descriptive and statistical methods. The results demonstrated strong content, face, and expert validity. Statistical analyses further supported construct validity, with correlation coefficients ranging from 0.881 to 0.953, and a significant discriminant validity t-test value of 21.4 (p < 0.01). The correlation between the newly developed scale and a criterion measure was 0.841, indicating a high level of concurrent validity.Reliability analyses revealed high internal consistency (Cronbach’s alpha = 0.917), split-half reliability (r = 0.892), and test-retest reliability (r = 0.926), confirming the scale’s robustness. The overall level of post-traumatic growth among the sample was moderate, with a mean rank score of 2.05 based on the study’s range-based scoring formula.
Keywords: Psychological Trauma; Post-Traumatic Stress Disorder (PTSD); Post-Traumatic Growth; Adults